Ética y medioambiente. Ensayo de hermenéutica referida al entorno - Villarroel, Raúl (Revista de Filosofía, 2007)
Taking distance from the classical expressions of environmental known to this day, this article presents a philosophical defense of the environment, based in a hermeneutic of nature regarded as a text, whose protagonist could be the disempowered subject in the new historical circumstances. Given the debasement of its ontological status and the gravity of the ecological crisis, this subject is impelled to critically reconsider its techno-scientific program, by which the natural environment is being ravaged, and to take responsibility for the consequences of its individual and collective action on the world.